THE IMPORTANCE OF CRAFT PRODUCTION IN THE RESTAURANT BUSINESS (Development Service Industry Management, 2024)
The article examines the importance of craft production in the restaurant business. The concepts of craft and craft production are examined. The main differences between craft and traditional restaurant establishments are characterized. It is noted that an important feature of craft restaurant establishments is the flexibility of the menu, which can change depending on the season and availability of ingredients. This makes it possible not only to ensure the freshness of dishes, but also to draw attention to new gastronomic ideas and techniques. The advantages of the craft approach in the restaurant business are clarified: the quality of ingredients and the uniqueness of taste, individuality and creativity in creating dishes, gastronomic experience and interaction with the visitor, opportunities for healthy eating, responsibility and ethics of production. A number of challenges and difficulties of craft production in the restaurant business are characterized, namely: high production costs, problems with supply and storage, changes in demand: difficulties with scaling, logistics and inventory management; lack of qualified personnel, regulation and certification, and independence and branding. The types of businesses for the production of craft products in the restaurant business are considered, namely, features, requirements, start and difficulties. It is concluded that craft production in the restaurant business can attract visitors with high quality and uniqueness of restaurant dishes, but also involves a number of organizational, financial and logistical difficulties that must be worked on to ensure the stability and profitability of the restaurant business.
Keywords: craft; craft production; craft product; restaurant business